Using Healthcare Services: Perspectives of Community‐Dwelling Aging Adults With Intellectual Disabilities and Family Members. Issue 1 (19th December 2018) - Baumbusch, Jennifer; Moody, Elaine; Hole, Rachelle; Jokinen, Nancy; Stainton, Tim
Abstract: The aging of adults with Intellectual Disability (ID) in the community resulting from deinstitutionalization signals a need for change in healthcare policy and services. This population is growing older at rates similar to the rest of the population, and individuals with ID often have multiple chronic illnesses and may experience young‐onset dementia, increasing their need to use healthcare services. However, it is widely recognized that currently healthcare services are ill‐prepared to meet the unique needs of this population as they age in their communities. The purpose of this study was to explore this issue from the perspectives of aging individuals with ID and family members (FMs). This study employed qualitative description as the method of inquiry and took place in British Columbia, Canada. Adults with ID age 40 years and older ( N = 21) and FMs ( N = 26) participated. Data were collected through focus groups and semistructured interviews. Thematic data analysis was conducted to generate the main study findings. Two overarching themes were identified. First, "the organization and culture of healthcare services in the community." This theme included issues such as age restrictions on health services, navigating health services, the culture of appointment‐making, and implications of living in rural settings, all of which influenced how individuals used healthcare services. Second, "interactions with healthcare providers" illustrated ways in which providers contribute to healthcare experiences. Many factors, both organizational and interpersonal, shape the experiences of aging individuals with ID using healthcare services in their communities. There continues to be a policy and service gap that can create unnecessary and avoidable difficulties in using healthcare services. Policies, service delivery, and education of healthcare providers need to be revisited in light of the unique needs of this population aging in the community in order to ensure healthcare is accessible.